Impact of stocking density and feeding regimen on broilers: performance, carcass traits and bone mineralisation - Simsek, U. G.; Ciftci, M.; Cerci, I. H.; Bayraktar, M.; Dalkilic, B.; Arslan, O.; Balci, T. A. (Taylor & Francis Ltd, 2011)
To evaluate the effects of different stocking densities (22.5, 18.75, 15, 11.25, 7.5 broilers/m(2)) in ad libitum (Al) and limited or pair feeding (Pf) regimens a total of 2550 Ross-308 chicks were taken. All the Pf groups were provided the same amount of feed per broiler, as determined for the Al-fed group with 22.5 broilers/m2. Daily weight gain and feed intake were reduced (P <= 0.001) as stocking density increased in the Al groups. Feed conversion ratios were worse (P <= 0.01) in the Pf groups. Carcass yield and mortality were not affected by density or feeding method. Length (P <= 0.001), width and bone mineral content levels (P <= 0.05) of the tibiotarsal bone were higher in the Al groups with no effect on bone mineral density (P > 0.05). It is concluded that feed consumption was adversely affected by stocking density resulting in poor growth and bone mineralisation.
Keywords: broiler; stocking density; feeding; performance; carcass; bone mineralisation